The influence of promotional mix on female consumers' buying behaviour / Goh Mei Ling ... [et al.] - Goh, Mei Ling; Ang, Elaine Hwee Chin; Tan, Seng Huat; Tay, Tiam Poh (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2021)
The skin care industry has become very competitive today. The demand for skin care products has grown rapidly due to the growth in the population of working females and the penetration of Korean culture among Malaysians. Hence, this study aims to investigate the influence of promotional mix on buying behaviour of female consumers towards skin care products. This study has recruited 200 female respondents from Melaka using convenience sampling. The data was collected using a set of selfadministered questionnaires. Advertising, sales promotion, direct marketing, personal selling and public relations were included in the research model to predict buying behaviour of female consumers towards skin care products. Data analysis which involves measurement model and structural model were performed using PLS-SEM. Sales promotion and public relation both influence buying behaviour significantly. Advertising, direct selling and personal selling, however, were found to be non-significant. The findings have thus implied that sales promotion and public relation are important factors of buying behaviour of female consumers towards skin care products. This study has provided valuable information and insightful input to the marketers of skin care products.